Effects of ulinastatin therapy in emergency severe multiple trauma: A single-center randomized controlled trial. Issue 7 (17th February 2023) - Xu, Haiting; Jiao, Wei; Zhang, Yunfei; Deng, Xiaoyan; Dai, Rongrong; Chen, Lei
Abstract : Background: Severe multiple traumas are one of the most common diseases and carry a significant financial burden with high disability and mortality. There are no effective drugs in the clinical management of severe multiple traumas, and there is an absence of evidence-based medicine concerning the treatment of severe multiple traumas. Methods: The present study explored whether ulinastatin (UTI) can improve the outcome of severe multiple traumas. The present research included patients who were hospitalized in intensive care units after being diagnosed with severe multiple trauma. Patients received UTIs (400, 000 IU) or placebos utilizing computer-based random sequencing (in a 1:1 ratio). The primary outcome measures were 30-day mortality, multiple organ dysfunction syndrome, inflammatory response, coagulation function, infection, liver function, renal function, and drug-related adverse effects. Results: A total of 239 individuals were classified into 2 groups, namely, the placebo group (n = 120) and the UTI group (n = 119). There were no statistically significant differences in baseline clinical data between the 2 groups. The 30-day mortality and multiple organ dysfunction syndrome in the UTI group were remarkably improved compared with those in the placebo group. UTI can protect against hyperinflammation and improve coagulation dysfunction, infection, liver function, and renal function. UTI patients had markedly decreased hospitalization expenditures compared with the placebo group. Conclusion: The findings from the present research indicated that UTIs can improve the clinical outcomes of patients with severe multiple traumas and have fewer adverse reactions.